Oral administration of Grifola frondosa affect lipid metabolism and insulin signaling pathway on BKS. Cg-+Leprdb/+Leprdb/OlaHsd mouse - Seong-Bo Yun; Dae-Young Kim (Journal of animal reproduction & biotechnology (Online), 2021)
Diabetic mellitus (DM) is a carbohydrate metabolic disorder that involves high blood sugar because insulin works abnormally. Type 2 diabetes accounts for most of them. However, diabetes treatments such as GLP-1 and DPP-4 inhibitors commonly caused side effects including gastrointestinal disorders. Grifola frondosa (G. frondosa) revealed various pharmacological effects in recent studies. It has a variety of anti-cancer polysaccharides through host-mediated mechanisms. D-fraction in G. frondosa has apoptotic effects, promoting myeloid cell proliferation and differentiation into granulocytes-macrophages. It has also been shown to reduce the survival rate of breast cancer cells. Though, no further study has been conducted on the specific effects of G. frondosa in the db/db mouse. Therefore, we would like to research the blood glucose improving effect of G. frondosa, a natural material, in type 2 diabetes model mouse, in this study. G. frondosa was administered to the disease model mouse (BKS.Cg-+Leprdb/+Leprdb/OlaHsd) for 8 weeks to monitor weight and blood glucose changes every week. And we evaluated anti-diabetes effects by checking biomarker changes shown through blood. Experiment did not show statistically significant weight differences, but control groups showed significantly higher weight gain than G. frondosa administered groups. We collected blood from the tail veins of the db/db mouse each week. As a result, the lowest blood sugar level was shown in the 500 mg/ kg group of G. frondosa. Glucose in the blood was examined with HBA1c, and 7.8% was shown in the 500 mg/kg administration group, lower than in other groups. These results suggest the potential improvements of diabetes in G. frondosa.